MEASURMENT OF EFFECT LEVELS ON UREASE ENZYME ACTIVITY IN SOILS UNDER DIFFERENT INCUBATION TIMES - Alyaa Abdulateef Jassim AL- Atrkgee; Mazin Faisal Said (Mesopotamia Journal of Agriculture)
A  factorial  experiment  was  conducted  in laboratory using complete randomize  design (CRD) to study the effect of urea fertilizer levels on urease enzyme activity and available nitrogen  in Bashika  and  Al-hawi soils under different incubation times. Results  showed  a significant increases in enzyme activity in Bashika soil as compared with Al-hawi soil of 25.93%. 100kgN.h-1 gave  a significant increasing in enzyme activity  as compared with 200 kgN.h-1 of 15%. Enzymes activity was increased with increasing incubation time till to 30 days, then after a significant depression in enzyme activity was noticed. Bashika soil gave a significant increases in available nitrogen as compared with Al-hawi soil of 23.55%. 200 kgN.h-1 gave a significant increases  in available  nitrogen as compared with 100 kgN.h-1 of 27.48%. Available nitrogen was increased with increasing incubation time till 45 days, which gave 53.34 ppm. However a significant decreases was noticed at 60 days of incubation.